2020
DOI: 10.1175/bams-d-18-0225.1
|View full text |Cite
|
Sign up to set email alerts
|

Reporting on Climate Change by Broadcast Meteorologists: A National Assessment

Abstract: Television weathercasters are uniquely situated to inform their audiences about the local impacts of global climate change and a growing number of them are adopting the role of climate change educator. We surveyed all American broadcast meteorology professionals in 2015 (N = 2,059; response rate = 22.6%), 2016 (N = 2017; response rate = 31.2%), and 2017 (N = 2,177; response rate = 22.1%) to assess weathercasters’ interest in reporting about climate change; if, where, and how they report about climate change; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A recent study found that exposing the TV audience to climate reporting by the weather presenter enhanced their understanding of climate change as a local problem (Feygina et al, 2020). In another survey, almost two-thirds of the weather forecasters that had reported on climate change indicated that they either received little, or positive feedback from the audience (Timm et al, 2020). Similarly, Australian weather presenters were seen as impartial and trusted sources, in contrast to general climate information which was viewed as "too politicized" (Holmes et al, 2017).…”
Section: The Research Literaturementioning
confidence: 99%
“…A recent study found that exposing the TV audience to climate reporting by the weather presenter enhanced their understanding of climate change as a local problem (Feygina et al, 2020). In another survey, almost two-thirds of the weather forecasters that had reported on climate change indicated that they either received little, or positive feedback from the audience (Timm et al, 2020). Similarly, Australian weather presenters were seen as impartial and trusted sources, in contrast to general climate information which was viewed as "too politicized" (Holmes et al, 2017).…”
Section: The Research Literaturementioning
confidence: 99%
“…Most Americans want to hear from weathercasters about climate change (Perkins et al 2017). Many weathercasters have responded to this opportunity by becoming active in climate reporting and education (Timm et al 2020), although some weathercasts continue to experience barriers to reporting about climate change (Meldrum et al 2017).…”
Section: Growth In Weathercaster Reporting About Climate Changementioning
confidence: 99%
“…More recently, however, much greater numbers of weathercasters have reported views that agree with the scientific consensus that humans are causing climate change (Maibach et al, 2017). Weathercasters have displayed an increasing willingness to address it on air, noting little opposition from watchers when they do (Timm et al, 2020).…”
Section: Climate Communication As Transmissionmentioning
confidence: 99%
“…Aside from the weather forecast, TV meteorologists have taken advantage of new and alternative forms of media ritual to allow them to talk to audiences about climate change, such as the more regular and personalized contact offered by social media, or magazine segments dedicated to environmental topics (Timm et al, 2020). Toohey-Morales found that the rise of social media in the mid-2000s offered him a new, parallel, forum for sharing information that allows him to respond to questions and share information about climate change even when there is no relevant connection to the weather that day (Toohey-Morales interview, 2018).…”
Section: Forming a Communitymentioning
confidence: 99%